Associations among trauma, depression, and alcohol use profiles and treatment motivation and engagement in college students. Issue 7 (3rd October 2018) - Borsari, Brian; Yalch, Matthew M.; Pedrelli, Paola; Radomski, Sharon; Bachrach, Rachel L.; Read, Jennifer P.
ABSTRACT: Objective: This study examined how profiles of alcohol use and symptoms of common mental health disorders (depression and posttraumatic stress disorder [PTSD]) influenced the perceived need for and actual seeking of different types of treatment (for alcohol versus psychological distress) in college student drinkers.Participants: Undergraduate students ( n = 164) were assessed between September 2009 and August 2015.Methods: We classified students into different symptom profiles using model-based clustering and compared these profiles on a variety of variables.Results: The cluster model yielded three profiles: Low Risk ( n = 66), Concomitant ( n = 35), and Heavy Drinking ( n = 63). Students in these profiles significantly differed in alcohol consumption, alcohol-related cognitions and problems, and perceptions of need and prior engagement in treatment.Conclusion: A variety of strategies can be used to engage students experiencing heavy drinking and/or mental health problems into treatment on campus.